PELEMBAGAAN PROGRAM PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT (PHBM) DAN DAMPAKNYA BAGI MASYARAKAT DESA HUTAN - Diah Puspaningrum (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
Research is aimed at (1) acknowledging and analyzing the Public Forest Resource Management institutionalization at Kemiri Village, Panti Subdistrict; and (2) examining and analyzing the impact of the Public Forest Resource Management on the forest rural inhabitant at Kemiri Village, Panti Subdistrict. Qualitative approach is used. Research type is case study on the coffee farmers who belong to LMDH (Lembaga Masyarakat Desa Hutan) at Kemiri Village, Panti Subdistrict. The determination of research area is managed by purposive sampling, at Kemiri Village, Panti Subdistrict. It is evident because it is a central region of coffee producer at Jember Regency. The purposively selected sample is then subjected to the snow ball sampling. Data are collected by methods such as in depth interview (unstructured interview). Data sources are primary and secondary data. The word, sentences, or direct expressions from key informant are also obtained. The data analysis method is Miles and Huberman’s (1992) interactive model. Throughput principle, qualitative data analysis is used during data collection. The analysis technique involves three activities but conducted simultaneously such (1) data reduction, (2) data presentation, and (3) conclusion (verification). The implementation of PHBM Program at Kemiri Village, Panti Subdistrict, is reviewed from the normative perspective. The compliance to the norm is evidence regardless the less validation on the norm. Good land management is still found through the presence of weeding. Other norms involve the prohibition against illegal logging and main plant destruction, or the participation to plant the standing trees. The PHBM Program provides an impact on the forest rural inhabitant, which is changing the social standard of the forest rural inhabitant. The social change is also found in the economic sector of the forest rural inhabitant, particularly to whom with land ownership in the forest and whom without. The impact felt by those with land seems greater because the program increases their welfare and their ability to meet the better life standard. People without land ownership can find the chance of employment by working as farming laborer for coffee farmer in the forest land. New entrepreneurs are emerged for post-harvest processing, including coffee ore milling and coffee processing to coffee powder. The economic development of the forest rural inhabitant stimulates structural modification in how the forest rural inhabitant manages/operates the forest land because the vertical mobility is made from the grassroots level community to the upscale community. Key Words: Forest, PHBM, Impact